Continuous Personal Competency Improvement by Remote Education - Phantip Vattanaviboon; Kulnaree Sirisali; Sudarat Manochiopinij; Wijit Wonglumsom; Pairoj Leelahakul; Sophon Sirisali (Agriculture and Natural Resources, 2006)
Quality assurance concept concerns not only non-human factors, but also human competency. In this study, we evaluated two phase competency assessments in hematological techniques from the same group of Thai laboratory staffs with 78% and 75% response rate. Laboratory staffs who participated in our program would receive informed consent forms and the assessment materials via mail. Cell and blood smear identifications and quality control process were assessed in the first phase. Case scenarios derived from improper answers of the first phase were tested in the second phase. The answers were assessed and graded as 3 levels (3 = very good, 2 = good and 1 = fair) and compared between both phases. The results showed an average grade of 2.27 ± 0.55 and 2.31 ± 0.29 for the first and second phase. The distribution of participant’s grade in the first and second phase were 42.4%, 47.2%, 10.4% and 30.0%, 68.8%, 1.2% for grade 3, 2, 1, respectively. This result implies the improvement of laboratory personal competency, especially those who earned a low grade demonstrated a dramatic improved (p<0.01).